Plant hormones and neurotransmitter interactions mediate antioxidant defenses under induced oxidative stress in plants - Raza, Ali; Salehi, Hajar; Rahman, Md Atikur; Zahid, Zainab; Madadkar Haghjou, Maryam; Najafi-Kakavand, Shiva; Charagh, Sidra; Osman, Hany S.; Albaqami, Mohammed; Zhuang, Yuhui; Siddique, Kadambot H. M.; Zhuang, Weijian (Frontiers in plant science, 2022)
Due to global climate change, abiotic stresses are affecting plant growth, productivity, and the quality of cultivated crops. Stressful conditions disrupt physiological activities and suppress defensive mechanisms, resulting in stress-sensitive plants. Consequently, plants implement various endogenous strategies, including plant hormone biosynthesis (e.g., abscisic acid, jasmonic acid, salicylic acid, brassinosteroids, indole-3-acetic acid, cytokinins, ethylene, gibberellic acid, and strigolactones) to withstand stress conditions. Combined or single abiotic stress disrupts the normal transportation of solutes, causes electron leakage, and triggers reactive oxygen species (ROS) production, creating oxidative stress in plants. Several enzymatic and non-enzymatic defense systems marshal a plant’s antioxidant defenses. While stress responses and the protective role of the antioxidant defense system have been well-documented in recent investigations, the interrelationships among plant hormones, plant neurotransmitters (NTs, such as serotonin, melatonin, dopamine, acetylcholine, and γ-aminobutyric acid), and antioxidant defenses are not well explained. Thus, this review discusses recent advances in plant hormones, transgenic and metabolic developments, and the potential interaction of plant hormones with NTs in plant stress response and tolerance mechanisms. Furthermore, we discuss current challenges and future directions (transgenic breeding and genome editing) for metabolic improvement in plants using modern molecular tools. The interaction of plant hormones and NTs involved in regulating antioxidant defense systems, molecular hormone networks, and abiotic-induced oxidative stress tolerance in plants are also discussed.